Protection of minority under the company law a comparative study / Ruziah Mohd - Mohd, Ruziah (Faculty of Law, 1987)
"It is not the business of the court to manage the affairs of the company. That is for the shareholders and directors. "It (the just and equitable provision) does, as equity always does, enable the court to subject the exercise of legal rights to equitable consideration; consideration, that is of a personal character between one individual and another, which may make it unjust or inequitable, to insist on legal rights, or to exercise them in a particular way. “Per Lord Wilber force in Ebrahimi v Westbourne Galleries Ltd. The above dicta expressed by the two of England foremost commercial judges represent judicial thinking on the rights of the minority shareholders, and demonstrate the progress made by such shareholders in securing greater protection over the years, culminating in the landmark decision of the House of Lords in Ebrahimi v Westbourne Galleries Ltd." It is axiomatic that a company acts in accordance with the decisions taken by the majority of its members, willing and able to vote yet, the minority cannot be completely ridden sough-shod. Hence, a proper balance of the rights of the majority and the minority is essential for the smooth functioning of the company.